Preliminary findings on the presence of a taxon with morphological traits of Papilio saharae Oberthür, 1879 in Lampedusa (Italy) (Lepidoptera: Papilionidae) - L. F. Cassar; A. Catania (SHILAP, 2022)
Research visits to the island of Lampedusa yielded a number of adult specimens belonging to the “machaoncomplex”, which, on closer examination of specific diagnostic features (including antennal segments, ocelli and number of teeth on the male harpe) have been found to possess morphological characters akin to Papilio saharae Oberthür, 1879, as well as to P. machaon Linnaeus, 1758, and including intermediate forms. Early stages, comprising ova and larvae, were also collected and reared, while several ova deposited by a gravid female taken in the field subsequently reached pupal stage. Ova are noticeably smaller, while larvae and pupae exhibit characters atypical of P. machaon. The present work examines a number of potential scenarios and provides a critique based on morphometric features of a suite of specimens examined, as well as on the history of eustatic sea-levels changes during the Quaternary Period that may potentially have abetted the species to reach Lampedusa during low-stands, before being left isolated during interglacial high-stands as sea-levels fluctuated during the Pleistocene epoch.